Growth and Yield of Mint (Mentha spicata L.) as Affected by Composition of Charcoal Husk and Organic Fertilizer - Pardono Pardono; A I Nurmalasari; P Harsono M. Mumtazul Fikri Nurfiansyah (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
The high industrial demand for mint products, coupled with low domestic production, has led to a 63% import dependency. Enhancing mint production requires optimizing planting media and fertilization strategies. This study aimed to evaluate the effects of different soil-to-husk charcoal ratios and manure types on the growth and yield of mint (Mentha spicata L.). A factorial experiment was conducted from February to April 2022 at the Faculty of Agriculture, UNS, using a randomized complete block design (RCBD) with two factors: The first factor was soil-to-husk charcoal ratios consisting of 1 to 3, 1 to 1, and 3 to 1. The second factor was the manure type, which consisted of cow, goat, and chicken manure. Each treatment was replicated four times. The results showed that the P1 combined with the cow manure significantly increased the number of branches compared to P1 with goat manure. P1 also resulted in the highest number of leaves, leaf area, fresh weight, and dry weight. Cow manure yielded the highest values for leaf number, leaf area, and dry weight among manure treatments. These findings suggest that optimizing planting media composition and manure selection can enhance mint productivity, reducing reliance on imports.